Digitalisasi Warisan Peradaban: Transformasi Budaya Islam dalam Era Revolusi Industri 4.0 - Ardhiansah, Arya; Alawi, Muammar; Jesinka; Arva Pratama, Mutiara; Saifullah, Iqbal (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2025)
This study explores the digital transformation of Islamic cultural heritage in the context of the Fourth Industrial Revolution. Employing a qualitative library research method and content analysis, the study investigates various forms of Islamic heritage digitalization, including textual materials (e.g., classical Islamic books), architectural heritage, and intangible cultural expressions. Key technologies such as artificial intelligence, virtual and augmented reality, blockchain, and cloud computing are analyzed for their roles in expanding access, preserving authenticity, and enhancing interactivity. Findings reveal a four-stage model of transformation: Digital Awakening, Digital Adaptation, Digital Integration, and Digital Innovation. These stages reflect the progression of digital engagement in Islamic learning, worship, and community life. The research highlights significant benefits such as democratized access to knowledge, improved cultural preservation, and new educational methods. However, it also identifies challenges including digital inequality, authenticity concerns, and the commodification of Islamic values. The study proposes a strategic framework based on five pillars: inclusive digital infrastructure, authoritative content curation, human resource development, cross-national collaboration, and ethical Islamic digital economy models. While offering theoretical and practical insights, the study acknowledges its limitation in empirical scope and recommends further research involving field-based data and interdisciplinary approaches to evaluate the impact of digital Islamic culture transformation in diverse sociocultural contexts.